Nucleation, Growth and Evolution of Hydroxyapatite Films on Calcite. Issue 1656 (21st August 2014) - Naidu, Sonia; Blair, Jeremy M.; Scherer, George W.
ABSTRACT: Marble, a non-porous stone composed of calcite, is subject to acid rain dissolution due to its relatively high dissolution rate. With the goal of preventing such damage, we have investigated the deposition of films of relatively insoluble hydroxyapatite (HAP) on marble. This paper investigates the factors that affect the nucleation and growth kinetics of HAP on marble. A mild, wet chemical synthesis route, in which diammonium hydrogen phosphate (DAP) salt was reacted with marble, alone and with cationic and anionic precursors under different reaction conditions, was used to produce inorganic HAP films on the mineral surface. Film nucleation, growth and metastable phase evolution were studied, using techniques such as scanning electron microscopy (SEM) and grazing incidence X-ray diffraction (GID). The onset of nucleation, and the growth rate of the film, increased with cationic (calcium) and anionic (carbonate) precursor additions. The calcium and phosphate precursors also influenced metastable phase formation, introducing a new phase.